Analysis of ADH1 protein expression in bacterial system - Nur'Ain Najwa, Bt Mohd Noor (Universiti Malaysia Sarawak (UNIMAS), 2012)
Alcohol dehydrogenase (ADH) is a group of gene involved in the oxidation of alcohols. Adhi cDNA that was derived from sago palm has been cloned into a bacterial expression vector, pET41a+ in order to obtain a high level expression of this recombinant in expression host E.coli XLI Blue and Rosetta II (DE3). Vector pET4Ia+ that has Adhi gene was transformed into E. coli by using heat shock transformations. The aim of this study was to express Adhi protein in bacterial system and the main focus of this research was to address the issues that affecting the heterologous proteins. The protein expression was optimized at different parameters which were the temperature and incubation time. The expressed protein was analyzed by SDS PAGE based on the total protein staining by using Coomassie Blue staining. The protein was successfully expressed in Rosetta II (DE3) strains based on the result from His-Tag purification.